Effects of cooling temperatures and low pH on membrane properties and voltage-dependent currents of rat nociceptive-like trigeminal ganglion neurons. Issue 1 (November 2018) - Viatchenko-Karpinski, Viacheslav; Gu, Jianguo G
Cooling temperatures and low pH have profound effects on somatosensory functions including nociception. The effects not only can be mediated by cooling temperature transducers and proton transducers expressed in subpopulations of somatosensory neurons but may also be mediated by ion channels involving membrane excitability such as voltage-dependent K + channels in somatosensory neurons. In the present study, we performed the in situ patch-clamp recordings from nociceptive-like trigeminal ganglion neurons in ex vivo trigeminal ganglion preparations of adult rats. We determined effects of cooling temperatures and low pH on membrane properties and voltage-dependent currents in nociceptive-like trigeminal ganglion neurons. Action potential rheobase levels were decreased when nociceptive trigeminal ganglion neurons were cooled from 24°C down to 12°C or when extracellular pH levels were reduced from 7.3 to 6. This indicates that the excitability of nociceptive-like trigeminal ganglion neurons was increased at the cooling temperatures and low pH. The decreases of action potential rheobase levels were accompanied by increases of trigeminal ganglion neuron input resistances at cooling temperatures and low pH, suggesting a possible involvement of background K + channels. Cooling temperatures and low pH suppressed voltage-activated inward Na + currents and also voltage-dependent outward K + currents in nociceptive-like trigeminal ganglion neurons. Voltage-dependent outward K + currents in nociceptive-like trigeminal ganglion neurons consist of inactivating A-type K + currents and non-inactivating type K + currents, and the former were more sensitive to cooling temperatures and low pH. Collectively, suppressing multiple types of K + channels may be associated with the enhanced excitability of nociceptive trigeminal ganglion neurons by cooling temperatures and low pH.